Digitalisation in grocery retailing in Germany: an exploratory study. Issue 5 (19th October 2020) - Piroth, Philipp; Rüger-Muck, Edith; Bruwer, Johan
ABSTRACT: This study examines German online grocery retailing structures, market participants and the degree of digitalisation in marketing services. This industry is characterised by a subpar share (0.9%) coupled with an above-average growth (20% from 2015 to 2017) thus making the market economically auspicious. This has attracted new competition with pure online players joining the market themselves or pairing with established logistic providers. While there is academic research on global online grocery retailing mostly on consumer behaviour and adoption, academic research for the German market with a changing environment due to globalisation and an ageing society, is very limited. This research, therefore, functions as a baseline study to allow further confirmatory research on the German market. We conducted an exploratory, qualitative study based on 20 in-depth interviews with industry experts. Data analysis was conducted using MAXQDA, Vers. 2018, that facilitated qualitative content analysis (QCA). We found that logistic issues (specifically the maintenance of the distribution cool chain) and technological infrastructure are viewed as key drivers of online grocery retailing. Furthermore, the degree of digitalisation within service processing can be improved This is especially true regarding an integrated and holistic customer experience from order to reception. Most online grocery retailers still lack a convincing online service and communication strategy. This is particularly true with regard to the communication of real-time delivery location and the integration of social functionality within their online offerings. Marketers should, therefore, adapt to these crucial and perceivable remarks from the experts perspective.